Elaboración de una crema nutritiva facial a base de la pulpa de Chirimoya (Annona cherimola, Annonaceae) -- Universidad Politécnica Salesiana, Unidad de Postgrado ; abril 2015 - Cobos Yanez, Diana Beatriz (2015)
The present study has for aim evaluate the cosmetic efficiency of a cream elaborated based on flesh of cherimoya (Annonna cherimola) since it agrees with the reports in the bibliography offers an excellent alternative to be used in the cosmetic industry for possessing big quantities of present vitamins. It split of three formulations in which changes the raw materials and the concentration of flesh; 5 %; 8 % to achieve a suitable formulation and of this to evaluate his efficiency. The flesh of cherimoya (Annonna cherimola) to 5 % inside the Unitary Formulation 1 (Formula 1B) is selected due to the fact that he presents fewer physical changes in comparison with other formulated ones, which allows to continue with the study of cutaneous compatibility (Patch test) in 30 volunteers, giving an Index of Primary Cutaneous Irritation equal (CONSUMER PRICES INDEX) to zero, by what the cream was tolerated well. With the purpose of verifying the power of wetting I evaluate the efficiency of the product in the same volunteers in two times later to the application of the cream: 2 hours and 24 hours, by means of the not invasive method using the equipment Corneómetro. There was verified that the cream elaborated based on flesh of cherimoya (Annonna cherimola) provides to the skin nourishing and wetting highly significant properties due to the benefits that this one presents, therefore according to the results and to the statistical analysis it expires with the wished properties and with the qualit indexes.